A119 AN EX VIVO MODEL TO STUDY THE GUT SEROTONERGIC SYSTEM RESPONSE TO LIVE AND HEAT-KILLED LACTOBACILLUS RHAMNOSUS STRAIN JB-1. (26th February 2020) - Javkar, T; Paul, M; Stanisz, A; Forsythe, P
Abstract: Background: Enterochromaffin (EC) cells are one of the most abundant enteroendocrine cells in the intestinal epithelium, responsible for producing and storing the largest pool of serotonin or 5-hydroxytryptamine (5-HT) in the body. 5-HT has been shown to be important for modulating a large number of gastrointestinal reflexes in health and disease. 5-HT can stimulate extrinsic (vagal and spinal afferents) or intrinsic primary afferent neurons (IPANs) which are involved in motility, secretion and vasodilation within the intestines. Where EC cell localized enzyme tryptophan hydroxylase (TpH) isoform 1 is responsible for 5-HT synthesis, serotonin reuptake transporter (Sert) and monoamine oxidase A (Mao A) are responsible for termination by uptake and metabolism of 5-HT respectively. Our previous research has demonstrated the effects Lactobacillus rhamnosus (JB-1) on the firing frequency of spinal nerve fibres and motility. Increasing interest is being focused on potential health benefits of heat-inactivated microbes and purified bacterial components. However, the effect of these heat-killed bacteria on the intestinal epithelium cells, particularly on EC cells, is unknown. Aims: Small intestinal organoids are shown to recapitulate in vivo characteristics of the small intestine epithelium. The present study aims to assess the suitability of intestinal organoids to study bacterial effects on the serotonergic system in the gut. Here we determined changes in the gene expression of key mediators in the serotonergic system [serotonin reuptake transporter (Sert), tryptophan hydroxylase-1 (Tph-1) and monoamine oxidase A (Mao A)] in response to live and heat-killed JB-1. Methods: Male C57bl/6 mice aged 6–8 weeks were used for both ex vivo and in vivo experiments. Jejunal organoids were grown from whole crypts isolated using DTT-EDTA solution. Live and heat-killed JB-1 bacteria were used as treatments. Gene expression analysis was performed on jejunal organoids and jejunum tissue using qRT-PCR. Results: JB-1 induced a significant increase in gene expression of Sert, Mao A and Tph-1. No significant difference was observed between the effects of live and heat-killed bacteria. In contrast the JB-1 increased expression of the peptide hormone CCK. Effects of JB-1 on gene expression in organoid culture were reflective of changes observed in in vivo experiments involving feeding of the bacteria. Conclusions: Ex vivo organoid culture could be a useful tool in studying mechanisms underlying bacterial effects on serotonergic signalling. The observation that heat-killed bacteria produced comparable effects to the live organism suggests the possibility of isolating active 5-HT modulating components from these strains. Future research will focus on identifying such bacterial components and how their effects on gene expression influence serotonin availability Funding Agencies: None